2019
DOI: 10.1007/s11695-019-04175-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes of Roux-en-Y Gastric Bypass and Sleeve Gastrectomy in Patients with Diabetes Mellitus: an Analysis of the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) Database

Abstract: Background The safety and efficacy of laparoscopic sleeve gastrectomy (LSG) and laparoscopic Roux-en-Y gastric bypass (LRYGB) to treat obesity and associated comorbidities, including diabetes mellitus, is well established. As diabetes may add risk to the perioperative period, we sought to characterize perioperative outcomes of these surgical procedures in diabetic patients. Methods Using the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) database, we identified patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…A total of 17,265 studies were retrieved, and 22 studies were eventually included ( 15 , 16 , 19 , 22 , 23 , 33 49 ). Details of the screening process are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 17,265 studies were retrieved, and 22 studies were eventually included ( 15 , 16 , 19 , 22 , 23 , 33 49 ). Details of the screening process are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The Revised Cardiac Risk Index included insulin-treated diabetes as a predictor of cardiac risk after non-cardiac surgery ( 20 ). Notably, although studies have reported higher short-term postoperative mortality in insulin-treated diabetes than in non-insulin-treated diabetes, there was no correlation between insulin-treated diabetes and postoperative mortality in multivariate logistic regression analysis ( 21 23 ). Another study also showed that in elderly patients with coronary artery disease or heart failure, insulin exposure 3 months before surgery was not associated with 30-day mortality after non-cardiac surgery ( 24 ).…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, extrapolating results assumes that the larger population of patients undergoing bariatric surgery have a similar distribution of prescription use for diabetes. Nevertheless, given that fewer than 1% of the eligible population undergo surgical treatment for obesity and metabolic disease in the US and only one-fourth of patients undergoing surgery are diagnosed with diabetes, we believe that there is an opportunity to decrease the financial and medical burden of diabetes …”
Section: Discussionmentioning
confidence: 99%
“…Non-Hispanic Black (NHB) (odds ratio [OR]: 1.56, 95% CI: 1.34-1.81) and Hispanic (OR: 1.29, 95% CI: 1.05-1.58) individuals have the highest risk of readmission post MBS compared with non-Hispanic White (NHW) (7). Type 2 diabetes has been shown to be a significant predictor of readmission, serious adverse events, and mortality post MBS (7)(8)(9)(10)(11)(12)(13).…”
Section: Study Importancementioning
confidence: 99%
“…Non‐Hispanic Black (NHB) (odds ratio [OR]: 1.56, 95% CI: 1.34‐1.81) and Hispanic (OR: 1.29, 95% CI: 1.05‐1.58) individuals have the highest risk of readmission post MBS compared with non‐Hispanic White (NHW) (7). Type 2 diabetes has been shown to be a significant predictor of readmission, serious adverse events, and mortality post MBS (7‐13). A recent study demonstrated that patients with type 2 diabetes who had undergone MBS had up to 15‐fold‐higher readmission rate compared with those without diabetes (14).…”
Section: Introductionmentioning
confidence: 99%